2021
DOI: 10.3390/ma14030488
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Biomaterial, Calcium Hydroxide and Chlorhexidine for Potential Use as Intracanal Medication

Abstract: The objective of this study was to develop a chitosan-based biomaterial with calcium hydroxide and 2% chlorhexidine for intracanal treatment application and, consequently, to diminish the number of microorganisms in the root canal system. The chitosan solution was prepared by dissolving it in 2% and 4% acetic acid (v/v) for 1 h at room temperature (25 °C) with magnetic agitation (430 rpm). Calcium hydroxide was obtained in two stages: the first was the synthesis of the calcium oxide—CaO, and the second was tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Silver was tested at concentrations ranging from 12.5 mg/L to 100 mg/L ( Figure 1 a–c,e–g), while CHX was tested using four different concentrations ranging from 0.5% (5 × 10 3 mg/L) to 4% (40 × 10 3 mg/L) ( Figure 1 d,h). Similar concentrations have been reported in the literature and correspond to 0.5×, 1×, and 2× MIC for silver and 0.25×, 0.5×, 1×, and 2× the most common concentration used in studies for CHX (2%) [ 7 , 24 , 30 , 31 , 47 , 48 ]. The time-kill kinetics profile of the drug-free CH paste (dotted line) indicated that there was a reduction in viable C. albicans cells but not of E. faecalis cells.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Silver was tested at concentrations ranging from 12.5 mg/L to 100 mg/L ( Figure 1 a–c,e–g), while CHX was tested using four different concentrations ranging from 0.5% (5 × 10 3 mg/L) to 4% (40 × 10 3 mg/L) ( Figure 1 d,h). Similar concentrations have been reported in the literature and correspond to 0.5×, 1×, and 2× MIC for silver and 0.25×, 0.5×, 1×, and 2× the most common concentration used in studies for CHX (2%) [ 7 , 24 , 30 , 31 , 47 , 48 ]. The time-kill kinetics profile of the drug-free CH paste (dotted line) indicated that there was a reduction in viable C. albicans cells but not of E. faecalis cells.…”
Section: Resultssupporting
confidence: 84%
“…Polymeric nanoparticles (PNPs) have been recently developed as sophisticated carriers for drug delivery [ 31 , 32 , 33 , 34 ]. They are comprised of active pharmaceutical ingredients that are adsorbed to or entrapped in a polymeric structure [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a wide spectrum of antimicrobial activity against Gram-positive and Gram-negative bacteria with almost no toxicity toward mammalian cells. [ 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%